2020
DOI: 10.1038/s41586-020-2398-2
|View full text |Cite
|
Sign up to set email alerts
|

Periodic activity from a fast radio burst source

Abstract: Fast radio bursts (FRBs) are bright, millisecond-duration radio transients originating from extragalactic distances 1 . Their origin is unknown. Some FRB sources emit repeat bursts, ruling out cataclysmic origins for those events [2][3][4] . Despite searches for periodicity in repeat burst arrival times on time scales from milliseconds to many days 2, 5-7 , these bursts have hitherto been observed to appear sporadically, and though clustered 8 , without a regular pattern. Here we report the detection of a 16.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
179
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(188 citation statements)
references
References 55 publications
9
179
0
Order By: Relevance
“…A particularly interesting discovery reported by the CHIME/ FRB Collaboration is the repeating source FRB 180916. J0158+65, which shows a 16.35 day modulation in its burst activity (CHIME/FRB Collaboration et al 2020). In Spring 2020, follow-up observations of FRB 180916.J0158+65 in the 300−400 MHz frequency range (Chawla et al 2020;Pilia et al 2020) provided the lowest-frequency detections of FRBs to date.…”
Section: Introductionmentioning
confidence: 97%
“…A particularly interesting discovery reported by the CHIME/ FRB Collaboration is the repeating source FRB 180916. J0158+65, which shows a 16.35 day modulation in its burst activity (CHIME/FRB Collaboration et al 2020). In Spring 2020, follow-up observations of FRB 180916.J0158+65 in the 300−400 MHz frequency range (Chawla et al 2020;Pilia et al 2020) provided the lowest-frequency detections of FRBs to date.…”
Section: Introductionmentioning
confidence: 97%
“…The recurrent FRB 180916 was recently shown by the CHIME/ FRB collaboration to exhibit a 16 day period of unknown origin (CHIME/FRB Collaboration et al 2020a). Again, although known Galactic magnetars offer no clear explanation for periodic behavior at this scale (with the possible exception of candidate magnetar 1E 1613485055, which has a measured period of 6.7 hr; de Luca et al 2006), reasonable variations in the properties of extragalactic magnetars (e.g., extremely slow rotation, precession, or presence in a binary) offer a potential explanation (Beniamini et al 2020;Levin et al 2020;Lyutikov et al 2020;Tong et al 2020;Yang & Zou 2020;Zanazzi & Lai 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(yellow; Law et al 2017; Gourdji et al 2019), the recently localized CHIME repeater FRB180916 (purple; Marcote et al 2020; CHIME/FRB Collaboration et al 2020a), and the apparently nonrepeating FRBs180924 (green, upper limits denoted by upside-down triangles; Bannister et al 2019), 190523 (brown; Ravi 2019), and 181112 (blue;Prochaska et al 2019). We have used quoted rates where possible(Law et al 2017;Gourdji et al 2019;CHIME/FRB Collaboration et al 2020a) and otherwise estimated Poissonian rates based on quoted field exposure times where available.…”
mentioning
confidence: 99%
“…Over the past few years, daily radio observations of the northern hemisphere sky in the 400-800 MHz frequency band with the Canadian Hydrogen Intensity Mapping Experi-ment(CHIME) transit radio telescope have led to discovery of many new repeatingFRB sources (The CHIME/FRB Collaboration et al 2019aFonseca et al 2020), enabled by the instrument's large instantaneous field of view(FoV), wide bandwidth, and high sensitivity (The CHIME/FRB Collaboration et al 2018). In particular, the discovery of FRB180916.J0158+65(also referred to as FRB 20180916B; The CHIME/FRB Collaboration et al 2019b), its subsequent localization to a nearby massive spiral galaxy (Marcote et al 2020), and the detection of a 16.35 day periodicity (or possibly a higher frequency alias of this period) in the burst arrival times (The CHIME/FRB Collaboration et al 2020a) have facilitated detailed studies of the source via follow-up observations across multiple wavelengths(e.g., see Scholz et al 2020;Tendulkar et al 2020). Most bursts from FRB180916.J0158+65 have been detected within a ∼5.4 day interval during cycles when the source was observed to be active (e.g., see Chawla et al 2020;Marthi et al 2020;Pilia et al 2020;Sand et al 2020;The CHIME/FRB Collaboration et al 2020a), but some bursts have been found to occur slightly outside this activity window (e.g., see Aggarwal & Realfast Collaboration 2020).…”
Section: Introductionmentioning
confidence: 99%